Analysis of prior knowledge elementary school students using three-tier diagnostic test to identify blood circular system misconceptions - Yusup Maulana; Wahyu Sopandi; Ika Rosmiati; Nurul Saadah Agustina (IAIN Palangka Raya, 2023)
This study aims to describe the initial understanding and identify elementary school students' misconceptions about the circulatory system. This research method is descriptive, with the research subject being 29 5th-grade students at an elementary school in Bandung Regency. The three-tier multiple-choice diagnostic test instrument used 7 items. Data on the results of the diagnostic test instrument are in the form of percentage calculation data and analysis of student answers. Students' initial knowledge is categorized into 3, namely Misconceptions (MK), Not Knowing Concepts (TTK), and Knowing Concepts (TK). The result of this study is the highest misconception (MK) was the concept of organs in the circulatory system, with a finding of 68.97%. The students who do not know the concept (TTK) are highest in the concept of organs in the circulatory system, with a finding of 72.41%. Students who know the concept (TK) are highest on the concept of blood group, with a finding of 82.76%. This research can be a reference for teachers to introduce the concept of the circulatory system, which can improve understanding and minimize students' misconceptions.Â Â